FESTIVAL MUSIK SOUNDRENALINE SEBAGAI PENGARTIKULASI JIWA MUDA REMAJA BALI - Darmawan, Komang Mulia; Nugroho, Wahyu Budi; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2020)
The increasing development of pop music has prompted the emergence of a music festival in Bali, namely the Soundrenaline music festival. There is a dialogical relationship that influences youth in particular to visit Soundrenaline. This study aims to describe and explain how Soundrenaline's articulation is for Balinese adolescents and Balinese adolescents' interpretation of Soundrenaline. This research uses a qualitative approach with an explanative descriptive type. The theory used in this research is the theory of cultural industry Theodor W. Adorno. The results of the field research show that the Soundrenaline music festival which has become a trend among teenagers has articulated teenagers from what has been displayed at the festival. As well as the adolescent interpretation formed by Soundrenaline's articulation, it makes adolescents consider Soundrenaline as a means of their pleasure. In the end, this unconsciously made Balinese teenagers dull in their critical power. Keywords: Articulation, Balinese adolescents, Soundrenaline music festival